LEGAL MEASURES FOR PROTECTING HOMEWORKERS: CASE STUDY OF DIGITALLY SKILLED WORKERS - Kiatsudakuekoon , Srisuda; Limprasert, Sanyapong (Journal of MCU Nakhondhat, 2023)
This research article aims to study the protection of digital homeworkers In other words, the Protection of Domestic Workers Act B.E.2010 and compare it with international law of the International Labor Organization and foreign law. Using a qualitative research method and study and research mainly from documents According to the study, Thailand's laws still have limitations preventing them from protecting digitally skilled workers. But it does not provide protection for digitally skilled homeworkers. Currently, the nature of the occupation has developed more than industrial work, resulting in other types of work that are not protected by this law. In addition, there is no provision in determining the remuneration of digitally skilled workers in this law. Because jobs related to digital technology require a lot of work skills and professional expertise. There is also no definition of "compensation" in this law. May cause problems in the interpretation of the law. When the home worker has completed the work, how should he be compensated? The law in this regard is not sufficient to protect home workers in the case of digitally skilled workers. Better digital so that Thai laws have been developed to be up to date and to cover digitally skilled homeworkers